014 Routine HIV testing in the Emergency Department: a tale of two trials. (14th September 2011) - Finlay, S; Rayment, M; Rae, C; Roberts, P; Sullivan, A
Abstract : Objectives and Backgrounds: The problem of undiagnosed HIV in the UK, resulting in preventable transmission rates, morbidity, mortality and cost, needs to be addressed. The HINTS ("HIV testing in Non-Traditional Settings") trial showed that HIV testing in the ED is acceptable to patients and successful in identifying previously undiagnosed individuals. We aim to establish a model for sustainable HIV screening in the ED. HEDsUP ("HIV Testing in Emergency Departments: A Universal Offer Programme") investigates ED-led delivery of testing within a network of four North West London EDs. Methods: We implemented 24/7 doctor-delivered testing of all 16–65-year-old ED patients able to consent, as a part of routine care. Patient information leaflets were given and promotional material displayed. Salivary tests collected in the ED were processed in the local virology laboratory. Patients received results by text message (negative result) or telephone call if test reactive to arrange confirmatory serology. Local sexual health services organised all follow-up. ED and Sexual Health staff met weekly to review key outcome measures (number of eligible patients, numbers of tests offered and accepted). Sustainability methodology (real time run charts, statistical control methods, plan-do-study-act cycles) was used to modify processes in an iterative fashion. Results: See Abstract 014 table below. Marked weekly variation was noted in all key outcome measures. Plan-do-study-act cycles with notable positive impact included introduction of local champions, in-house teaching, and increased prominence of promotional material. Conclusions: HIV testing in EDs is feasible and remains acceptable (arguably more so) when doctor-delivered. Main challenges identified were expanding and maintaining provision across all shifts and all staff. An IT solution to prompt further testing is planned. Further work is underway to identify barriers to testing through focus groups and 1:1 interviews.